2016
DOI: 10.1177/1077801216662342
|View full text |Cite
|
Sign up to set email alerts
|

Professional Help-Seeking for Adolescent Dating Violence in the Rural South: The Role of Social Support and Informal Help-Seeking

Abstract: Structural equation modeling with three waves of data was used to assess a mediation model investigating the relationship between perceived social support, informal help-seeking intentions, and professional help-seeking intentions in the context of adolescent dating violence. The sample included 589 adolescents from a rural, southern county who participated in a longitudinal study of teen dating violence victimization and perpetration. Results suggest that informal help-seeking intentions are an important link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 57 publications
4
35
1
5
Order By: Relevance
“…Haynie et al. () similarly found that females who were victims of both physical and verbal dating violence had more pronounced negative outcomes compared with females who were victims of verbal dating violence only. While it appears that physical and sexual dating violence may have more severe negative effects than psychological dating violence, particularly for females, it is clear that adolescent dating violence of any kind has significant implications for adolescent well‐being and therefore is a serious public health concern.…”
Section: Adolescent Dating Violence Effects and Prevalencementioning
confidence: 99%
See 4 more Smart Citations
“…Haynie et al. () similarly found that females who were victims of both physical and verbal dating violence had more pronounced negative outcomes compared with females who were victims of verbal dating violence only. While it appears that physical and sexual dating violence may have more severe negative effects than psychological dating violence, particularly for females, it is clear that adolescent dating violence of any kind has significant implications for adolescent well‐being and therefore is a serious public health concern.…”
Section: Adolescent Dating Violence Effects and Prevalencementioning
confidence: 99%
“…Dating violence is psychoemotional, physical, or sexual violence within a dating relationship (St. Mars & Valdez, ). As many as one third of adolescents report being a victim of some form of dating violence (Cyr, McDuff, & Wright, ; Foshee et al., ; Halpern, Oslak, Young, Martin, & Kupper, ; Haynie et al., ; Mulford & Giordano, ). Prevalence rates have varied from study to study due to differences in the types of violence asked about on surveys, age ranges of participants, and survey administration (Ocampo, Shelley, & Jaycox, ).…”
Section: Adolescent Dating Violence Effects and Prevalencementioning
confidence: 99%
See 3 more Smart Citations